Metabolic Syndrome Is Associated With Advanced Liver Fibrosis Among Pediatric Patients With Non-alcoholic Fatty Liver Disease - Ting, Yi-Wen; Wong, Sui-Weng; Anuar Zaini, Azriyanti; Mohamed, Rosmawati; Jalaludin, Muhammad Yazid (Frontiers in Pediatrics, 2019)
Background: Non-alcoholic fatty liver disease (NAFLD) among children is a growing concern with potential significant outcome. This study aims to investigate the relationship between hepatic steatosis, metabolic syndrome and liver fibrosis among children with obesity and diabetes mellitus. Methodology: Children aged 6-18 years old were recruited from pediatric obesity and diabetes clinic in University Malaya Medical Centre (UMMC) between year 2016 and 2019. Data on basic demographics, anthropometric measurements and clinical components of metabolic syndrome were collected. Transient elastography was performed with hepatic steatosis and liver fibrosis assessed by controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) respectively. Mild, moderate and severe steatosis were defined as >248 dB/m,>268 dB/m and>280 dB/m respectively, and LSM above 7.0 kPa for fibrosis stage F≥2, 8.7 kPa for F≥3 and 10.3 kPa for F4 (cirrhosis). Results: A total of 57 children (60% male) with median age of 13 years old were recruited. Fifty (87.7%) of the children are obese and 27 (54%) out of 50 are morbidly obese. Among 44 (77.2%) patients with steatosis, 40 (70.2%) had severe steatosis and 18 (40.9%) had developed liver fibrosis of stage 2 and above. Advanced fibrosis or cirrhosis was detected in 8 (18.2%) children with presence of steatosis. Twenty-three out of 57 (40.4%) was diagnosed with metabolic syndrome. Fibrosis is three times more likely to occur in the presence of metabolic syndrome (OR=3.545, 95% CI: 1.135-11.075, p=0.026). Waist circumference is a significant predictor of fibrosis after multiple regression analysis. Conclusion: Obese children with metabolic syndrome are more likely to have advanced liver fibrosis compared to those without metabolic syndrome. Waist circumference predicts development of liver fibrosis.